Impact assessment on DFS supplementation Post NHE on nutrient intake of critically anemic pregnant mothers in a tribal set up of Gujarat - Nair, S; Bandyopadhyay, S; Skaria, L (Indian Journal of Community Health, 2014)
Introduction: Adequate nutrition is essential during pregnancy to ensure optimal fetal growth. Especially maternal Iron and Iodine deficiency have negative and irreversible effects of the developing fetus. Double Fortified Salt (DFS) with both iodine and iron was later proposed by NIN to be simple and inexpensive public health strategy to control iron and iodine deficiencies. Efficacy trials were run by Nair et al., 2007 using DFS showed a beneficial effect on population by an increase of 4-5% change in the iron status of the highly malnourished subjects. Objectives: The study has focused on the impact of DFS along with nutrient intake on critically anemic pregnant mothers in tribal areas of Jhagadia with 58% of preterm deliveries. Materials and Methods: Present study was carried out in Bharuch District. From this area 135 pregnant mothers were enrolled. NHE regarding consumption of DFS and dietary improvement was provided. Reinforcement was carried out after 1 month of supplementation with DFS. Results: Out of 135 subjects, 40% were UIC deficient, 75% were moderately anemic, 15% and 10% were mild and severely anemic respectively. DFS (1mg iron and 40ppm iodine/g) supplementation and Nutrition Health Education for 2 months showed statistical non-significant change in UIE and iron status of the pregnant mothers. Significant increment in both macro and micro nutrient intake from pre to post intervention period was observed. Conclusion: Owing to the fact that dietary contribution of Iron was only 7mg/day, it is clearly evident that even DFS and IFA supplementation showed no significant improvement in iron status. Dense nutrition is the key element for improving maternal nutritional status.